Performance of Calcium Chloride- Ammonia Adsorption Refrigeration System - John, Michael; Kimambo, Cuthbert Z. M.; Nydal, Ole J.; Kihedu, Joseph H. (Tanzania Journal of Engineering and Technology, 2021)
An experimental study on the performance of calcium chloride-ammonia adsorption system is described. A single bed water cooled condenser adsorption refrigerator prototype, which utilises calcium chloride-ammonia pair has been developed and tested in the laboratory. Experiments have been conducted for desorption temperatures of 100 °C with desorption time varying from 1 to 4 hours. An electric tape heater and a timer were used to perform the experiments. The adsorption temperature profile, adsorption rate and prototype performance have been analysed and discussed. The tested heating and desorption temperature of 100 °C and heating and desorption time of 1 to 4 hours was able to create a cooling effect of the cold chamber of the prototype of between -0.8 to 8.3 °C, which is adequate for vaccine storage requirement of 2 to 8 °C. The estimated Coefficient of Performance of the system ranges between 0.025 and 0. 076. Keywords: Adsorption, Ammonia, Calcium chloride, Refrigeration.